Artificial Intelligence and Health Communication: Utilisation of "SIMPATI" Application in Accelerating Stunting Management in Sumedang Regency - Suminar, Jenny Ratna; Prasanti, Ditha; Aisha, Sarah (Jurnal Ilmu Komunikasi, 2024)
The purpose of this study is to determine how the health communication process, using the SIMPATI application, accelerates stunting management in Sumedang, and to identify the barriers to health communication during the use of SIMPATI.  According to presidenri.go.id, Munir (2023) mentioned that a technology-based application called the Integrated Stunting Prevention System (SIMPATI) contributed to stunting management in Sumedang. This phenomenon is unique and warrants study, as it relates to achieving the vision of Indonesia Emas (Golden Indonesia) 2045: a nation free from stunting. How has Sumedang leveraged Artificial Intelligence (AI). Among many regions in Indonesia, Sumedang is making new breakthroughs through AI to reduce stunting. Thus, the purpose of this study is to determine the health communication process using SIMPATI application in accelerating stunting management in Sumedang; and to find out health communication barriers during the use of SIMPATI. This research employs a qualitative approach using a case study method. Data were collected through observation, literature review, and in-depth interviews. The results showed that the health communication process was carried out by the Sumedang government through optimizing digital media. The existence of AI in the SIMPATI application is seen as a step to accelerate the reduction of the stunting rate in Sumedang.Researchers found that health communication components were optimized in this case. The SIMPATI application was socialized by trained health communicators to convey the message of 'stunting reduction' in Sumedang. The barriers to AI in Sumedang Regency’s health communication include technical, personal, language, and cultural barriers